2014
DOI: 10.2489/jswc.69.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of agroforestry and time on soil and water conservation of sloping red soil in southeastern China

Abstract: Soil and water loss from plots were recorded over five years (2001 to 2005) in an experiment comparing five different agricultural treatments on sloping red soil. Results showed that Bahia grass (Paspalum notatum Flugge) cover was an important factor for soil preservation, despite the presence of citrus tree planting or alley cropping in plots. The traditional rotation system (soybean [Glycine max L.]-radish [Raphanus sativus L.]) was shown to be unsuitable for soil and water conservation. However, changing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…Since the selected site factors include both qualitative and quantitative factors, and the ranges and magnitudes of values are not consistent, this study used a field survey to quantify and standardize the site factors in order to eliminate the influence of the ranges and magnitudes of the values, so that the results are comparable. The quantification of site factors used the degree of influence on the strength of vegetation recovery to assign a score to each factor (Zhao, 2008;Wang et al, 2009;Li et al, 2015) and the quantification of the factors is shown in Table 1.…”
Section: Quantification Of the Site Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the selected site factors include both qualitative and quantitative factors, and the ranges and magnitudes of values are not consistent, this study used a field survey to quantify and standardize the site factors in order to eliminate the influence of the ranges and magnitudes of the values, so that the results are comparable. The quantification of site factors used the degree of influence on the strength of vegetation recovery to assign a score to each factor (Zhao, 2008;Wang et al, 2009;Li et al, 2015) and the quantification of the factors is shown in Table 1.…”
Section: Quantification Of the Site Factorsmentioning
confidence: 99%
“…In this study, according to the special topography of the mine waste dump, the index evaluation system was established by combining the factors of topography, soil and vegetation. The factor analysis method (Li et al, 2015) was used to quantify and standardize the site factors based on the factor quantification in Table 1 along with the extreme difference standard method, and then the weights of each factor were determined and finally calculate the composite score by the weights. The formula is as follows:…”
Section: Site Quality Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…After a reversal linear transformation derived from training samples, the relationship between C and NDVI can be establish [18]. Meanwhile, the values of P was estimated and assigned to the corresponding land cover using Spot image 2010 of Cameron Highlands.…”
Section: Sediment Yield In Gis Environmentmentioning
confidence: 99%